Communal-based domestic rainwater harvesting system: A novel approach to alternative solutions for increasing water supply and recharging groundwater in Jagakarsa urban area, South Jakarta - Suprapti Suprapti; Muhammad Syahril Badri Kusuma; Hadi Kardhana; Muhammad Cahyono; Imroatul Chalimah Juliana (Case Studies in Chemical and Environmental Engineering)
This study proposes a new approach, a communal-based domestic rainwater harvesting (CDRWH) system, which is a new model that combines domestic and communal rainwater harvesting systems. This model is an alternative solution to improve system performance and utilize rainwater overflow from the system. Rainwater runoff from several domestic tanks is channeled to a communal tank to be collected, processed, and redistributed to needy domestic tanks. Overflow from the communal tank is used for groundwater recharge. The CDRWH system model aims to increase water supply, reduce runoff, and conserve groundwater. The model simulation uses daily water balance analysis and yield before spillage algorithm. The simulation scenario uses variations in roof area, number of house occupants, storage tank volume, and rainfall categories: 20 years, wet year, normal year, and dry year. Jagakarsa, an urban area in South Jakarta, was selected for the CDRWH system modeling. The results showed that the CDRWH model significantly improved the performance of the volumetric reliability (VR) and time reliability (TR) systems. In addition, the model could show a comparison of total groundwater recharge (GWR) and groundwater extraction (GWE), where the GWR capacity was higher. This allows centralized rainwater management in communal tanks, thereby reducing groundwater usage. The design of this model is simple. Therefore it can be easily duplicated for application in other locations.